Citizen Strangers: Identity Labelling and Discourse in the French Mandatory Syria, 1920–1932 - Abrahamyan, Victoria (My University, 2020)
This article explores the roles played by Armenian refugees in the politics of identity in Mandatory Syria by examining how their arrival shaped the discourses of inclusion and exclusion. It does so by analysing three key events: the Armenians’ access to citizenship and voting rights (1924–1925), the Great Syrian Revolt (1925–1927), and the arrival of new Armenian refugees (1929–1930) – during which a ‘Syrian’ identity was gradually confirmed against the Armenian newcomers. Making use of discursive narratives by Syrian and Armenian political parties, media outlets and pamphlets, the article demonstrates that the discourse against the Armenian refugees played a decisive role for both hosting and incoming communities to construct mutually excluding national identities. If the Arab nationalists used the anti-Armenian discourse as an opportunity to define a ‘Syrian’ national identity closely identified with Islam and Arabness, similarly, it was used by the Armenian political elite to mobilise Armenian refugees.
Keywords: Syria; refugees; state-building; discourse; identity construction; nationalism